Historical Clinical Outcomes of Children with Myelomeningocele Meeting the Criteria for Fetal Surgery: A Retrospective Cohort Survey of Brazilian Patients - Peixoto-Filho, Fernando Maia; Cervante, Tatiana Protzenko; Bellas, Antonio Rosa; Gomes Junior, Saint Clair; Lapa, Denise Araújo; Acácio, Gregório Lorenzo; Carvalho, Paulo Roberto Nassar de; Sá, Renato Augusto Moreira de (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To analyze the historical clinical outcomes of children with myelomeningocele (MMC) meeting the criteria for fetal surgery, but who underwent postnatal primary repair.Methods Data from children undergoing postnatal MMC repair between January 1995 and January 2015 were collected from the Neurosurgery Outpatient Clinic's medical records. Children were included if they had ≥ 1 year of postoperative follow-up and met the criteria for fetal surgery. The children's data were then stratified according to whether they received a shunt or not. The primary outcome was mortality, and secondary outcomes were educational delays, hospitalization, recurrent urinary tract infections (UTIs), and renal failure.Results Over the 20-year period, 231 children with MMC were followed up. Based on clinical data recorded at the time of birth, 165 (71.4%) qualify of fetal surgery. Of the 165 patients, 136 (82.4%) underwent shunt placement. The mortality rate was 5.1% in the group with shunt and 0% in the group without, relative risk (RR) 3.28 (95% confidence interval, 95% CI, 0.19–55.9). The statistically significant RRs for adverse outcomes in the shunted group were 1.86 (95% CI, 1.01–3.44) for UTI, 30 (95% CI, 1.01–537) for renal failure, and 1.77 (95% CI, 1.09–2.87) for hospitalizations.Conclusion Children with MMC qualifying for fetal surgery who underwent shunt placement were more likely to have recurrent UTIs, develop renal failure, and be hospitalized. Since approximately half of the shunt procedures could be avoided by fetal surgery, there is a clinical benefit and a possible financial benefit to the implementation of this technology in our setting.
Keywords: meningomyelocele; fetal surgery; myelomeningocele; cerebrospinal fluid shunts; spinal dysraphism